2018
DOI: 10.1507/endocrj.ej17-0496
|View full text |Cite
|
Sign up to set email alerts
|

Divergent patterns of genic copy number variation in <i>KCNIP1</i> gene reveal risk locus of type 2 diabetes in Chinese population

Abstract: Abstract. Copy number variation (CNV) has emerged as another important genetic marker in addition to SNP for understanding etiology of complex disease. Kv channel interacting protein 1 (KCNIP1) is a Ca 2+ -dependent transcriptional modulator that contributes to the regulation of insulin secretion. Previous genome-wide CNV assay identified the KCNIP1 gene encompassing a CNV region, however, its further effect and risk rate on type 2 diabetes (T2D) have rarely been addressed, especially in Chinese population. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Also associated with the 5 cap region in the ILHV genome, miRNA hsa-mir-4693, according to functional enrichment analysis, has been linked as a regulator of the targets KCNIP1 and ARRB2. Both of these targets are associated with the regulation of regulatory subunits of type A cellular potassium channels, which modulate the excitability of neuronal membranes, agonist-mediated desensitization of G protein-coupled receptors, and mediate the processes of desensitization and resensitization of cellular receptors to hormones, neurotransmitters, and immune signaling, respectively [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Also associated with the 5 cap region in the ILHV genome, miRNA hsa-mir-4693, according to functional enrichment analysis, has been linked as a regulator of the targets KCNIP1 and ARRB2. Both of these targets are associated with the regulation of regulatory subunits of type A cellular potassium channels, which modulate the excitability of neuronal membranes, agonist-mediated desensitization of G protein-coupled receptors, and mediate the processes of desensitization and resensitization of cellular receptors to hormones, neurotransmitters, and immune signaling, respectively [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance (IR) is dened by the WHO as a common ground for T2DM and various complications caused by it. 26,27 Currently, the "second strike" doctrine of oxidative stress has occupied the core position of IR research. Studies have shown that oxidative stress not only originates from IR, but also damages islet b cells and aggravates lipid metabolism disorder.…”
Section: Discussionmentioning
confidence: 99%
“…1A and B, the copy numbers of the PTPN22 gene were detected by Exon7-probe1, Exon12-probe2, and Intron17-probe3, and the same tendency of the copy number variations was investigated between the T2D patients and controls. Furthermore, quantitative PCR (qPCR) method was used to confirm the copy number as described by our previous study [8]. The CN types were classified as gain (>0.5), loss (<-0.5) and normal (<| ±0.5|) based on the log 2 2 -ΔΔCt values.…”
Section: Detection and Verification Of The Ptpn22 Cnv In Chinese Populationmentioning
confidence: 99%
“…CNVs also play important roles in modeling complex human diseases. Extensive CNVs evaluation studies have identified significant associations between CNVs and diseases such as schizophrenia [4], tumor [5,6], and endocrine metabolism disorders [7,8] using the candidategene approaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation